2019
DOI: 10.5603/cj.a2018.0047
|View full text |Cite
|
Sign up to set email alerts
|

Impact of left atrial appendage closure on cardiac functional and structural remodeling: A difference-in-difference analysis of propensity score matched samples

Abstract: Background: Although the safety and efficacy of left atrial appendage (LAA) closure (LAAC) in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Previous literature reported opposite effects on left atrial volume changes between AF ablation and LAAC, [ 25 , 26 ] that AF ablation led to decreased left atrial volume (reverse remodeling) [ 25 ] while LAAC induced left atrial enlargement (remodeling). [ 26 ] Therefore, LAAC with concomitant ablation might benefit patients by reversing LAAC-induced left atrial remodeling, which was supported by our previous study using cardiac CT-based evaluation. [ 27 ] However, the reverse remodeling has not been detected by the TTE follow-up in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature reported opposite effects on left atrial volume changes between AF ablation and LAAC, [ 25 , 26 ] that AF ablation led to decreased left atrial volume (reverse remodeling) [ 25 ] while LAAC induced left atrial enlargement (remodeling). [ 26 ] Therefore, LAAC with concomitant ablation might benefit patients by reversing LAAC-induced left atrial remodeling, which was supported by our previous study using cardiac CT-based evaluation. [ 27 ] However, the reverse remodeling has not been detected by the TTE follow-up in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with significant LA structural reverse remodeling following AFCA have better LA function, and may indicate more efficient LV filling pattern and better cardiac function . On the other hand, latest studies have shown a significantly increased LAV after LAAC . It was also pointed out that the LA enlargement was unlikely to be caused by structural remodeling due to AF, as AF load did not significantly increase during follow‐up .…”
Section: Discussionmentioning
confidence: 99%
“…Patients studies have shown a significantly increased LAV after LAAC. 8,9 It was also pointed out that the LA enlargement was unlikely to be caused by structural remodeling due to AF, as AF load did not significantly increase during follow-up. 8 It is thus evident that AFCA and LAAC exert opposite effects on LA size, with the former resulting in LA structural reverse remodeling while the latter exacerbating the remodeling process.…”
Section: Simple Linear Regression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Also, LAAO induced left atrium size increasing and left ventricular filling pressure need further study. 80) …”
Section: Left Atrial Appendage Occlusion In Asian Populationsmentioning
confidence: 99%